Subtilases: a major prospect to the genome editing in horticultural crops - Chandrasekaran, Umashankar; Hong, Woo Jong; Kim, Hyeran (Frontiers in Plant Science, 2025)
Plant peptides, synthesized from larger precursor proteins, often undergo proteolytic cleavage and post-translational modifications to form active peptide hormones. This process involves several proteolytic enzymes (proteases). Among these, SBTs (serine proteases) are a major class of proteolytic enzymes in plants and play key roles in various regulatory mechanisms, including plant immune response, fruit development and ripening, modulating root growth, seed development and germination, and organ abscission. However, current knowledge about SBTs is largely limited to ‘in vitro cleavage assays,’ with few studies exploring loss of function analyses for more in depth characterization. Research focused on economically significant horticultural crops, like tomato and pepper, remains scarce. Given this, leveraging SBTs for horticultural crop improvement through advanced gene-editing tools is critical for enhancing crop resilience to stress and pathogens. Over the past five years, research on proteolytic enzymes, especially SBTs, has increased markedly, yet reports involving loss- or gain-of function analyses aimed at improving crop yield and quality are still limited. This review summarizes recent findings on SBT enzymes, which act as ‘protein scissors’ in activating peptide hormones, and discusses the potential for using selected SBTs in CRISPR-Cas9 gene editing to enhance the growth and resilience of economically important Solanaceae crops, with a focus on pepper.